Patient participation as an integral part of patient-reported outcomes development ensures the representation of the patient voice: a case study from the field of rheumatology. Issue 1 (5th August 2015) - de Wit, M P T; Kvien, T K; Gossec, L
Abstract : Introduction: Patient-reported outcomes (PROs) are important instruments to evaluate healthcare interventions, both in clinical practice and clinical research. Objective: To describe how representation of the perspective of people with psoriatic arthritis was obtained through active participation on different levels in the development of PROs. Methods: This case study focuses on the methods of involving patients in the elaboration and validation of the Psoriatic Arthritis Impact of Disease (PsAID) score. We used the concept of the participation ladder and the European League Against Rheumatism (EULAR) recommendations for the involvement of patient representatives in scientific projects to analyse the variety of ways patients participated in this process. Results: Two patient experts were part of the steering group. 12 patient research partners, coming from 12 different European countries, participated in identifying domains, formulating items for the questionnaire and determining the number of items, the recall period and the questionnaire format. They also helped with the translation of the items into different European languages. Then, 139 patients took part in ranking and prioritising the domains for importance; 65 patients were involved in cognitive debriefing interviews; 499 new patients were recruited for the validation study. Challenges of patient participation in PRO development, such as the representation of patients, are discussed. Conclusions: Making patient participation an integral part of the PRO development and validation process is an important requisite for outcome research. The variety of patient contributions at different phases in this case study resulted in an instrument with high face validity.